Public administration digitalization and government effectiveness in the EU countries - Androniceanu, Armenia (Central European Public Administration Review, 2023)
Purpose: This study continues the series of previous research carried out by the authors on digital transformation in the EU countries. It aims to identify and analyse the progress made by EU administrations in terms of digitization and effective governance in the period 2019–2021. Design/methodology/approach: Based on selected variables from Eurostat and the World Bank databases, the article provides insights into the dynamic changes that occurred in the EU in the period under consideration. The research employs Principal Component Analysis (PCA) and K-means clustering as the primary research methods to analyse the variations and correlations among 10 numerical variables selected from Euro-stat and World Bank databases. Findings and Practical Implications: The results obtained through PCA show the impact of digitalization on government effectiveness. A comprehensive analysis of government effectiveness has been conducted using PCA, which reveals that the first two principal components account for 77.05% of the initial variance. A K-means clustering with four clusters reveals that the most significant and noteworthy increase in digitalization and government effectiveness in the EU is achieved by the Nordic countries, which exhibit high levels of digitalization and government efficiency. Originality: In this ranking, clusters 2 and 3 comprise well-developed countries with a positive relation between governmental digitalization and efficiency, while cluster 4 consists of emerging countries where the correlation between digitization and governmental efficiency is low or very low, which is primarily attributed to the limited degree of digitization within government institutions.
Keywords: analiza glavnih komponent; digital transformation; digitalizacija; digitalization; digitalna preobrazba; government effectiveness; javna uprava; principal component analysis; public administration; učinkovitost vlade